Desarrollo profesional de las secretarias y su impacto en la gestión del departamento de Talento Humano del Gobierno Autónomo Descentralizado del cantón Vinces - García Suárez, Mayling Carolina (2021)
The focus of this case study will determine the impact of professional development in the management of the human talent department of the decentralized government of Vinces canton, Los Ríos province. The inquiry was carried out through descriptive research, after pertinent analysis. It was possible to observe the characteristics of the variables that are being studied, after an exhaustive study proposal were established to solve the problem, thus the institution acquires commitment and responsibility on the part of the secretaries as a result. For the execution of this study, the survey was applied as an instrument, being this used in the secretaries of the same, in this way it has been possible to establish strategies for professional development. Career planning and self-improvement is one of the main needs of the human being, this is sometimes achieved by voluntary efforts or by the support of the institution where he works, applying feedback is substantial so that the collaborators of an establishment feel motivated and valuable in their work environment, so that this will have a positive influence on the management of human talent, because the secretaries will be qualified to manage, motivate and develop greater effectiveness and efficiency in the collaborators.